What can cetacean stranding records tell us? A study of UK and Irish cetacean diversity over the past 100 years. Issue 4 (30th April 2019) - Coombs, Ellen J.; Deaville, Rob; Sabin, Richard C.; Allan, Louise; O'Connell, Mick; Berrow, Simon; Smith, Brian; Brownlow, Andrew; Doeschate, Mariel Ten; Penrose, Rod; Williams, Ruth; Perkins, Matthew W.; et al.
Abstract: There are many factors that may explain why cetaceans (whales, dolphins, and porpoises) strand. Around the UK and Ireland, over 20, 000 stranding records have been collected since 1913, resulting in one of the longest, continuous, systematic stranding data sets in the world. We use this data set to investigate temporal and spatial trends in cetacean strandings and use generalized additive models (GAMs) to investigate correlates of strandings. We find a dramatic increase in strandings since the 1980s, most likely due to increases in recording effort, and the formation of formal strandings networks. We found no correlation between the numbers of cetaceans stranding each year and several potential environmental and anthropogenic predictors: storms, geomagnetic activity, North Atlantic Oscillations, sea‐surface temperature, and fishing catch. We suggest that this is because the scale of change in the variables is too coarse to detect any potential correlations. It may also highlight the idiosyncratic nature of species' responses to external pressures, and further the need to investigate other potential correlates of strandings, such as bycatch and military sonar. Long‐term cetacean stranding data provide vital information on past and present diversity for common, rare, and inconspicuous species. This study underlines the importance of continued support for stranding networks.